Proceedings of 1995 Conference on Electrical Insulation and Dielectric Phenomena
DOI: 10.1109/ceidp.1995.483759
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of positive streamers over insulating surfaces in air

Abstract: The positive streamer in air has been shown to exhibit reproducible properties which can be measured precisely in a uniform electric field; examples are the field are the field required for its propagation and its velocity as a function of field. It is thus an excellent tool for assessing the influence of the material upon discharge propagation over insulating surfaces. The paper compares streamer propenies in air alone with those when propagated over a surface in a uniform field. In the latter case, streamers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…This effect has been attributed in [3] to the results of photo-emission of electrons from the insulator surface by UV light from the formative avalanches. It has been demonstrated by Gosho et al [12] and Verhaart et al [7] and proposed also as the reason for the higher velocities of streamers over insulating surfaces, compared with those in air [5]. However, there is a more rapid decay of the corona current, which is attributed to an electron current, indicated by the half-width measurements of Figure 8.…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…This effect has been attributed in [3] to the results of photo-emission of electrons from the insulator surface by UV light from the formative avalanches. It has been demonstrated by Gosho et al [12] and Verhaart et al [7] and proposed also as the reason for the higher velocities of streamers over insulating surfaces, compared with those in air [5]. However, there is a more rapid decay of the corona current, which is attributed to an electron current, indicated by the half-width measurements of Figure 8.…”
Section: Methodsmentioning
confidence: 49%
“…More recently, studies of the pre-breakdown discharges have attempted a more fundamental approach. Thus, the work of Gallimberti et al [3] and Windmar [4] in non-uniform field configurations and of Allen and colleagues [5,6] in uniform fields have attempted to display the properties of streamers when propagated along insulating surfaces. The basic properties of avalanches in proximity with insulating surfaces have been investigated by Verhaart and colleagues [7,8], providing valuable insights into the formative stages of corona on surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the gathered knowledge comes from electrical engineers, who have been troubled by this phenomenon for years [2][3][4][5][6][7][8][9][10] because material interaction with the streamer development is of significance when it comes to insulation performance. For the most part, their research was done in air and in atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Allen and Ghaffar [2] showed that the streamers usually propagate in two modes-there is a fast component over the dielectric surface and a slow one in ambient air. They offered an explanation, saying that the ionization rate was altered in the presence of an insulator because of electrons emitted from the dielectric surface by photoemission and detachment of negative ions.…”
Section: Introductionmentioning
confidence: 99%
“…Allen et al [13], [14], [15] studied the propagation of streamers across a parallel-plate air gap bridged by different solid insulators, 12 cm thick (insulator materials included Teflon, nylon and glazed ceramic). The streamer was formed by imposing a positive pulsed voltage on a point electrode located in a small aperture cut in the anode.…”
Section: Past Workmentioning
confidence: 99%